SHMT2 Desuccinylation by SIRT5 Drives Cancer Cell Proliferation - Yang, Xin; Wang, Zhe; Li, Xin; Liu, Boya; Liu, Minghui; Liu, Lu; Chen, Shuaiyi; Ren, Mengmeng; Wang, Yankun; Yu, Miao; Wang, Bo; Zou, Junhua; et al. (Cancer research (Chicago, Ill.), 2018)
The mitochondrial serine hydroxymethyltransferase SHMT2, which catalyzes the rate-limiting step in serine catabolism, drives cancer cell proliferation, but how this role is regulated is undefined. Here, we report that the sirtuin SIRT5 desuccinylates SHMT2 to increase its activity and drive serine catabolism in tumor cells. SIRT5 interaction directly mediated desuccinylation of lysine 280 on SHMT2, which was crucial for activating its enzymatic activity. Conversely, hypersuccinylation of SHMT2 at lysine 280 was sufficient to inhibit its enzymatic activity and downregulate tumor cell growth in vitro and in vivo. Notably, SIRT5 inactivation led to SHMT2 enzymatic downregulation and to abrogated cell growth under metabolic stress. Our results reveal that SHMT2 desuccinylation is a pivotal signal in cancer cells to adapt serine metabolic processes for rapid growth, and they highlight SIRT5 as a candidate target for suppressing serine catabolism as a strategy to block tumor growth. Significance: These findings reveal a novel mechanism for controlling cancer cell proliferation by blocking serine catabolism, as a general strategy to impede tumor growth. Cancer Res; 78(2); 372–86. ©2017 AACR.